2014
DOI: 10.1088/0031-9155/59/6/1353
|View full text |Cite
|
Sign up to set email alerts
|

Use of the BIPM calorimetric and ionometric standards in megavoltage photon beams to determineWairandIc

Abstract: The BIPM graphite calorimeter standard for absorbed dose to water has been used in conjunction with an ionization chamber of known volume and with Monte Carlo simulations of these arrangements to determine the value for Wair in (60)Co radiation and in accelerator photon beams up to 25 MV. The results show no evidence for a variation in Wair at the 0.2% level over this energy range. Taking the constancy of Wair as established, the best estimate is Wair = 34.03 eV with a standard uncertainty of 0.21%. Consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 17 publications
(25 reference statements)
4
22
0
Order By: Relevance
“…Of note, DL also reported measurements for depths well beyond the electron practical range in graphite, i.e., where energy deposition is due to electrons set in motion by secondary bremsstrahlung photons rather than primary electrons. Analysis of this photon regime data yields W air values which also compare favorably with recent values obtained using x‐ray beams produced by clinical linacs …”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Of note, DL also reported measurements for depths well beyond the electron practical range in graphite, i.e., where energy deposition is due to electrons set in motion by secondary bremsstrahlung photons rather than primary electrons. Analysis of this photon regime data yields W air values which also compare favorably with recent values obtained using x‐ray beams produced by clinical linacs …”
Section: Introductionsupporting
confidence: 76%
“…could suggest that W air in fact exhibits an energy dependence for electrons with energies from a few MeV to 15 MeV; strictly speaking, this possibility still cannot be excluded. However, the data do not join in a satisfactory way to the well‐established results for 10 keV electrons, 60Co γ ‐rays, and MV x‐ray beams; hence the dependence is considered anomalous.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…k Q,Q 0 factors were calculated for a wide range of plane-parallel ionization chambers and a limited set of cylindrical ionization chambers. Two different sets of mean excitation energy 110 values for water (I w ) and graphite (I g ) were used: (i) the ICRU 37 (ICRU 1984) andICRU 49 (ICRU 1993) values currently in use (I w = 75 eV and I g = 78 eV); and (ii) the latest I-values for water (I w = 78 eV, Andreo et al 2013) and graphite (I g = 81.1 eV, Burns et al 2014), to be recommended in a forthcoming ICRU report on key data for ionizing radiation dosimetry. Two different W air values for proton beams were also used 115 accordingly (Andreo et al 2013).…”
mentioning
confidence: 99%
“…W air has been extensively measured for low energy beams, under 1 MeV, for both photon and electron sources, but measurements with megavoltage beams are limited, with only one data set each published for high‐energy electron and photon beams as shown in table 5.6 of ICRU report 90 . Cojocaru et al reported a single value of W air 33.84(14) eV in high‐energy electron beams (15 to 50 MeV) and Burns et al obtained 34.03(7) eV in high‐energy photon beams (6 to 25 MV).…”
Section: Introduction and Purposementioning
confidence: 99%